C/EBP-δ regulates VEGF-C autocrine signaling in lymphangiogenesis and metastasis of lung cancer through HIF-1α - Min, Yongfen (2011)
CCAAT/enhancer-binding protein delta (C/EBP-δ), a transcription factor, is elevated in carcinoma compared to normal tissue. This study reports a novel function of C/EBP-δ in lymphangiogenesis and tumor metastasis. Genetic deletion of C/EBP-δ in mice resulted in a significant reduction of lymphangiogenesis and pulmonary metastases, with a dramatic reduction of VEGF-C and its cognate receptor VEGFR3 in lymphatic endothelial cells (LECs). In contrast, no difference of VEGF-C in tumor tissues and bone marrow was observed between null and wild type mice. Consistently, forced expression of C/EBP-δ increased VEGF-C and VEGFR3 expression in cultured LECs. These findings suggest a specific and important role of C/EBP-δ in regulating VEGFR3 signaling in LECs. Furthermore, expression of C/EBP-δ in cultured LECs significantly increased cell motility, and knockdown of C/EBP-δ inhibited cell motility and lymphatic vascular network formation in vitro. Forced expression of VEGF-C, but not recombinant VEGF-C, rescued knockdown of C/EBP-δ-induced cell apoptosis, indicative of autonomous VEGF-C autocrine signaling essential for LEC survival. Moreover, hypoxia induces C/EBP-δ expression, and C/EBP-δ regulates HIF-1α expression. Blocking HIF-1α activity totally blocked CEBP-δ induced VEGF-C and VEGFR3 expression in LECs. Together, these findings reveal a new function of CEBP-δ in lymphangiogenesis via regulating VEGFR3 signaling in LECs.